PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIB SDN 011BANJAR XII KEC. TANAH PUTIH - Hardati, Hardati; Kurniaman, Otang; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The problem this research is the student achievement of social studies fifth graderes SDN 011 Banjar XII still low with an average value of 58,75 and minimum completenness criteria (KKM) social studies is 70. Between students, amounting to 16 people only 6 students who achieve classical KKM with 37,5%. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Formulation of the problem : is the implementation of cooperative learning model type Numbered Heads Together (NHT) can improve students achievment of social studies at SDN 011 Banjar XII. The research was conducted on march 19, 2015 to april 23, 2015by 2 cyclees. Subjects were students of SDN 011 Banjar XII, totalling 16 people who use the data source. The data collection instruments in this research is a teacher and students activities sheets and students achievement. Based on the conduct of research with the implementation of learning models obtained results koopertif NHT type of activity the teacher in the lerning process in cycle I frist meeting was 54,2% and at the second meeting of teacher activity increased by 79,2% so become 25,0%. cycle II firs meeting and the second meeting of activity increased by 87,5 and the second meeting of activity increased by 95,8 so become 8,3%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 58,3 and at second meeting of activity increased 79,2 so become 20,9% and a second meeting of activity increased 87,5 at the firs meeting of the second meeting of activity increased 91,7 so become 42,7%. This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 58,75. In the first cycle improve an average of 73,75 with increase as 25,23% and an impove in the second with an average of 83,44 with increase as 42,03%. Result in the research that the implementation of cooperative learning model of Numbered Heads Together (NHT) can improve students achievement of social Studies at fifth graderes SDN 011 Banjar XII Kecamatan Tanah Putih.Key Words : Model Numbered Heads Together, Fave graderes students Achievement